Inspiratif, Aktif Dan Menyenangkan : Pembelajaran PKn Dengan KUBUSPKn Berbasis Website: - Eneng Martini; Moh Fadli Alfikri (Universitas Palan, 2023)
The problems found in civics learning indicate a decrease in student learning motivation with a decrease in the level of children's participation in doing tasks given by teachers, besides that this is caused by changes in education policies during the transition period of the Covid-19 pandemic so that this changes the learning paradigm. This study aims to determine the level of effectiveness of using KUBUSPKn on student learning motivation in PPKn subjects at SMK PGRI 1 Cimahi. The research method in this study uses the correlation method to determine the relationship of variables. The sampling technique in this study used random sampling. The results of this study were shown from the results of the t-test analysis of t count 7.168> t table 1.662 which indicated a significant influence between independent variables and dependent variables, obtained results from F-count 51.386 > F table 3.953) so that based on the results of the study the use of CubePkn has a significant value that affects student learning motivation.